Improvement of continuous technology of electrochemical synthesis of nickel hydroxide by implementation of solution recycling - Kovalenko, Vadym; Kotok, Valerii (Eastern-European Journal of Enterprise Technologies, 2021)
Nickel hydroxide is widely used in supercapacitors, alkaline batteries, for the electrocatalytic oxidation of organic contaminants, etc. Due to their electrochemical activity, Ni(OH)2 (α+β) samples with a layer structure synthesized in a slit diaphragm electrolyzer are the most promising. To improve the continuous technology of electrochemical synthesis of nickel hydroxide, the possibility of recycling the spent catholyte containing sodium sulfate was determined. For this, samples of nickel hydroxide were synthesized from a solution of nickel sulfate in the presence of sodium sulfate with concentrations of 40, 60, 80, 100, and 120 g/L. The crystal structure of the samples was studied by X-ray phase analysis; the electrochemical properties were studied by the method of cyclic voltammetry. It was shown that the base sample obtained without the presence of sodium sulfate was a monophase layered (α+β) structure with a high content of α-modification. The crystallinity of the sample was not high. It was revealed that the presence of sodium sulfate led to a decrease in the crystallinity of nickel hydroxide due to an increase in the electrical conductivity of the solution and a decrease in the voltage in the electrolyzer. Cyclic voltramperometry showed that synthesis in a slit diaphragm electrolyzer in the presence of Na2SO4 (40–80 g/L) did not lead to a significant change in the electrochemical activity of nickel hydroxide samples. An increase in the concentration of sodium sulfate in the catholyte to 100–120 g/L led to an increase in electrochemical activity – the specific current of the discharge peak was 3.7–3.9 A/g (compared to 2.1 A/g for the reference sample). A comprehensive analysis of the characteristics of nickel hydroxide samples synthesized in the presence of sodium sulfate revealed the possibility and prospects of recycling the spent catholyte in a continuous technology for producing Ni(OH)2 in a slit diaphragm electrolyzer. It was revealed that when introducing recycling, it was recommended to maintain a high concentration of sodium sulfate (80–100 g/L)